Development and application of a multiplex TaqMan real-time PCR assay for detecting pathogenic fungi causing root rot in red kidney bean - Liu, Wenbo; Peng, Xurong; Li, Hanwei; Kang, Huiting; Zhao, Jie; Yang, Chun; Zhao, Xiaojun; Hao, Xiaojuan (Frontiers in Plant Science, 2025)
Fusarium root rot poses a significant threat to red kidney bean (Phaseolus vulgaris) production in Shanxi Province, China, and is primarily caused by Fusarium oxysporum, Fusarium tricinctum, and Fusarium solani. Currently, no method exists for the rapid and simultaneous detection of these three pathogens. In this study, we developed a multiplex TaqMan real-time PCR assay targeting the translation elongation factor 1-alpha (TEF-1α) gene. Specific primers and probes were designed based on conserved regions within TEF-1α. The assay demonstrated high specificity and sensitivity, with detection limits of 1.46 × 10³, 7.17 × 10³, and 1.76 × 10² copies·μL-1 for F. oxysporum, F. tricinctum, and F. solani, respectively. Intra- and inter-assay variability tests showed high reproducibility, with coefficients of variation below 2%. Field surveys conducted in Shanxi’s main production areas assessed the root rot disease index, and corresponding soil samples were collected. A logistic regression model was established to predict disease index based on the total DNA copy number of the three pathogens per gram of soil: y= 100−96.670/ [1 + (x/7.253)9.350] (R2 = 0.927). This multiplex TaqMan real-time PCR assay provides a rapid, specific, and reproducible tool for simultaneous detection of these Fusarium pathogens, supporting early disease intervention and reducing crop losses in red kidney bean.